Preoperative hypocalcemia predicts postoperative complications in older orthopedic patients: A multicenter cohort study - Doudou Li; Ting Zhang; Yanmei Ning; Jiacong Miao; Jiana Shi; Ying Hu (PLoS ONE, 2026)
Background Serum calcium, a key biochemical marker in the body, plays a crucial role in maintaining bone health. Nevertheless, research exploring the link between preoperative serum calcium levels and the occurrence of postoperative complications in elderly orthopedic patients is currently lacking. Aims This study sought to assess the ability of preoperative serum calcium levels to predict the occurrence of postoperative complications in geriatric orthopedic surgery. Methods We utilized multivariate logistic regression to identify correlations between serum calcium levels and complications. Generalized additive models to analyze the dose-response relationship with curve fitting and threshold effect evaluation. Subgroup analyses further evaluated the impact of other covariates. Results This study included 690 elderly patients undergoing orthopedic surgery. Common postoperative complications primarily included infection, hypoalbuminemia, and electrolyte imbalance, etc. The study demonstrated that preoperative serum calcium levels were an independent protective factor against postoperative complications (OR: 0.24, CI: 0.07–0.76, P = 0.036). When comparing groups based on serum calcium tertiles, patients in the low calcium group exhibited a 79% higher risk of complications compared to the high calcium group (OR = 1.79, 95% CI: 1.12–2.78). Further nonlinear relationship analysis revealed a threshold effect between serum calcium and postoperative complication risk, with a turning point at 2.4 mmol/L. The association was statistically significant below this value but not above it. Subgroup analyses and interaction tests showed that age, gender, comorbidities, and medications, cognitive function, cardiac function, and surgical complexity were not significantly associated with this correlation (P > 0.05 for interaction). Conclusion Preoperative calcium screening and correction may represent a simple, low-cost strategy to reduce postoperative complications in elderly orthopedic patients. This study provides evidence for the importance of actively correcting calcium levels before surgery and establishes the value of serum calcium as an early warning indicator for poor prognosis.